Diesel engine performance operating with tire derived fuel - Mohd Herzwan, Hamzah; Azri, Alias; R., Mamat; Abdul Adam, Abdullah; Sudrajad, Agung; Nur Atiqah, Ramlan; Nur Fauziah, Jaharudin (EDP Sciences, 2018)
Fossil fuel is non-renewable energy. This type of energy sources are widely used in many critical areas such as industrial application and vehicle application. Realizing this fact, many researches are conducted to produce alternative energy sources to reduce the dependence to fossil fuel for energy generation. As for example, fuels that produced from natural sources such as palm, rapeseed and jathropa are commonly used as alternative fuel especially for transportation purpose. Apart from natural sources, waste source such as used tires also can be utilized to produce alternative fuel. In this paper, the engine performance of diesel engine operating with unblended tire derived fuel (TDF) are analyzed and compared to diesel fuel. The experiment is conducted using a single cylinder, direct injection diesel engine. The engine operates at variable engine speed while constant load exerted to the engine. The performance parameters that are analyzed in the experiment includes engine power, engine torque, combustion pressure and exhaust gas temperature. Results from the experiment shows that diesel engine can operate with unblended TDF. However, TDF is not suitable for high engine speed applications. Furthermore, TDF produce lower performance output compared to diesel fuel.